RUMAH SUSUN SEDERHANA SEWA KELURAHAN PELINDUNG HEWAN (RUSUNAWA PELWAN) - Nurasili, Renita Ayuandra; Wijaya, Karto; Rahmat, Amat (Jurnal Arsitektur ARCADE, 2022)
Abstract: The rate of population growth in Indonesia is growing very rapidly, but this is not accompanied by the availability of adequate decent housing. Limited land in urban areas in Indonesia is one of the important issues behind the unavailability of decent housing for all groups. The decent housing that has been built offers prices that are not affordable for most people. This certainly needs to find a solution so that all people can still get decent housing by utilizing limited urban land, especially for people with middle to lower economic levels or Low Income Communities (MBR). Land efficiency by making residential terraces up or vertical can be a low-cost housing solution for MBR. Through the role of architecture in creating vertical settlements in the form of flats that meet standards, the concept of Pragmatic Architecture which prioritizes aspects of function over aesthetics is considered capable of answering the findings of certain problems that are real and measurable such as population density, limited land, allocation of funds, supporting facilities for the needs of daily residents. day, structure & construction and various other aspects. It is hoped that this functional design will be effective in improving the quality of life for the occupants of the flats in order to provide decent housing in limited urban land.Abstrak: Laju pertumbuhan penduduk di Indonesia berkembang sangat pesat namun hal ini tidak diiringi dengan ketersediaan hunian layak yang memadai. Keterbatasan lahan di perkotaan di Indonesia menjadi salah satu isu penting dibalik tidak tersedianya hunian layak bagi semua kalangan. Adapun hunian layak yang terbangun menawarkan harga yang tidak terjangkau bagi sebagian besar masyarakat. Hal ini tentu perlu dicari solusi agar seluruh kalangan masyarakat tetap mendapatkan hunian layak dengan memanfaatkan lahan perkotaan yang terbatas terkhusus bagi masyarakat dengan tingkat ekonomi menengah kebawah atau Masyarakat Berpenghasilan Rendah (MBR). Efisiensi lahan dengan membuat hunian bersusun keatas atau vertikal dapat menjadi solusi hunian murah bagi MBR. Melalui peran arsitektur guna menciptakan pemukiman vertikal berupa rumah susun yang memenuhi standar, konsep Arsitektur Pragmatik yang memprioritaskan aspek fungsi diatas estetika dinilai mampu menjawab temuan permasalahan tertentu yang nyata adanya serta dapat diukur seperti kepadatan penduduk, keterbatasan lahan, pengalokasian dana, fasilitas penunjang kebutuhan penghuni sehari hari, struktur & konstuksi dan berbagai aspek lainnya. Harapan dari desain yang fungsional ini dapat efektif dalam meningkatkan kualitas hidup penghuni rumah susun dalam rangka memberikan hunian layak di keterbatasan lahan perkotaan.